Islamization of Malay Language and its Role in the Development of Islam in Malaya - Mabruroh Mabruroh; Rosyidatul Khoiriyah (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The spread of Islam in the Indonesian archipelago not only influences social change, but also on language development. One of the languages used in the archipelago at this time is Malay language. Malay language is a global language and plays a major role in the spread of Islam. Arabic and Malay language have the same position in generating language contact. These occurrence in language contact present a balance of two languages which results in the exchange of both language. This discussion is written in descriptive method. In addition, this discussion explains the influence of Islam on the development of Malay language and the Islamization of its language which then changed the Malay peoples perspective on life in accordance with the Islamic views and provided an enormous role in the development of Islam in Malay Country.